NeRF in the Wild: Neural Radiance Fields for Unconstrained Photo Collections - Martin-Brualla, Ricardo; Radwan, Noha; Sajjadi, Mehdi S. M.; Barron, Jonathan T.; Dosovitskiy, Alexey; Duckworth, Daniel (Proceedings (IEEE Computer Society Conference on Computer Vision and Pattern Recognition. Online), 2021)
We present a learning-based method for synthesizing novel views of complex scenes using only unstructured collections of in-the-wild photographs. We build on Neural Radiance Fields (NeRF), which uses the weights of a multi-layer perceptron to model the density and color of a scene as a function of 3D coordinates. While NeRF works well on images of static subjects captured under controlled settings, it is incapable of modeling many ubiquitous, real-world phenomena in uncontrolled images, such as variable illumination or transient occluders. We introduce a series of extensions to NeRF to address these issues, thereby enabling accurate reconstructions from unstructured image collections taken from the internet. We apply our system, dubbed NeRF-W, to internet photo collections of famous landmarks, and demonstrate temporally consistent novel view renderings that are significantly closer to photorealism than the prior state of the art.